Circulating cell-free DNA and IL-10 from cerebrospinal fluids aid primary vitreoretinal lymphoma diagnosis - Zhuang, Zhe; Zhang, Yan; Zhang, Xiao; Zhang, Meifen; Zou, Dongmei; Zhang, Li; Jia, Congwei; Zhang, Wei (Frontiers in Oncology, 2022)
Primary vitreoretinal lymphoma (PVRL) is a rare variant of primary central nervous system lymphoma (PCNSL) that presents diagnostic challenges. Here, we focused on circulating cell-free DNA (cfDNA) and interleukin-10 (IL-10) isolated from cerebrospinal fluid. 23 VRL patients (17 PVRL, 2 PCNSL/O and 4 relapsed VRL, from 2018-10 to 2021-12) and 8 uveitis patients were included in this study. CSF samples from 19 vitreoretinal lymphoma patients had sufficient cfDNA for next-generation sequencing. 73.7% (14/19) had at least one meaningful non-Hodgkin lymphoma related mutation. The characteristic MYD88L265P mutation was detected in the CSF of 12 VRL patients, with a sensitivity, specificity, PPV, and NPV of 63.2%, 100%, 100% and 46.2%, respectively. No meaningful lymphoma related mutations were found in CSF samples from uveitis controls with typical intraocular lesions. Meanwhile, CSF IL-10 levels were elevated in 95.7% of the VRL patients, with a sensitivity, specificity, PPV and NPV of 95.7%, 100%, 100% and 88.9%, respectively. Key somatic mutations like MYD88L265P and CD79B detected from CSF cfDNA, as well as elevated CSF IL-10 levels can be promising adjuncts for primary vitreoretinal lymphoma diagnosis.